The use of an e-tongue for discriminating ethanol/water mixtures and determination of their water content - De Queiroz, Dalton P. [UNESP]; Florentino, Ariovaldo De Oliveira [UNESP]; Bruno, Juliana Catarina [UNESP]; Da Silva, José H. Dias [UNESP]; Riul, Antonio [UNESP]; Giacometti, José A. [UNESP] (Elsevier, 2016)
This paper discusses the applicability of an electronic tongue (e-tongue) based on capacitance measurements to determine the water content in ethanol. The e-tongue consisted of an array of interdigitated electrodes coated with ultrathin films of gallium nitrate and titanium dioxide, which were robust against attack by ethanol. Principal Component Analysis (PCA) was used to treat the capacitance data for discriminating ethanol/water mixtures even in cases with very small water contents. Discrimination is easier if the water added to ethanol contains ions, as is the case of tap water or if NaCl is added to the mixtures. With this e-tongue we were able to quantify the water content through a linear relationship between the first principal component (PC1) and the added water to the biofuel. Therefore, we have proven to be possible to measure the water content precisely, which is one of the major problems in ethanol biofuel adulteration nowadays.
Keywords: Electronic tongue; Ethano-water mixture; Ethanol biofuel; Principal component analysis